BEHAVIOR OF DRUG TRAFFICKING IN CAR - Kulpreeyawat, Tarin (Journal of MCU Nakhondhat, 2023)
This research article aims to study behavior of drug trafficking in a car and to study weighing evidence in the case where drugs were found in car. This documentary research is composed of gathered data from the Supreme Court’s judgments, statutory provisions and textbooks. The findings revealed that the case where the drug was found hidden in car, the Supreme Court held that the car was used in committing a crime, so it must be confiscated according to the Criminal Code, Section 33 (1). But in the case where drug was found apparently in a car, such as on the dashboard or on the car floor behind the driver’s seat. The Supreme Court held that the car was not used directly in committing a crime, therefore it cannot not be forfeited. As for weighing evidence in the case where drugs were found in car, the court must consider the testimony of prosecution witnesses, which are police officers in the raid, normally two or three witnesses are required to testify. The testimony of witnesses must not differ in material matters. If the testimony of witnesses differs materially, the court will consider the testimony to be suspicious, and do not listen to the testimony of plaintiff’s witnesses. Researcher has two suggestions as follow. Firstly, drug should be placed in car cabin, and any part of car should not be modified in order to transport drug. Secondly, police officers in the raid should rehearse their testimony one day before the testimony day in order not to testify on any material differences.